Penapis larraini Packer, a new species of rophitine bee (Hymenoptera: Halictidae) from a fog oasis in Northern Chile - Packer, Laurence (Zootaxa, 2012)
Penapis larraini Packer, sp. nov. (Hymenoptera: Halictidae: Rophitinae), is described from Alto Patache, South ofIquique, a fog oasis in the very dry coastal desert region of northern Chile. It is compared to other species of the genus, and its unusual foggy habitat is described.